Affect in Literary Translations: What is at Stake for the Author and the Translator - Klaarika Kaldjärv (Interlitteraria)
This article explores the relationships between authors, translators, and readers within the context of literature and translation. Emphasising the reciprocal influence between texts, it delves into the desire of writers to control the interpretation of their works during translation. The examination extends to the hierarchy within literature and translation, questioning whether a translated text can be considered an autonomous entity and if translators can be acknowledged as authors considering the transformative nature of translation and the subjective, creative processes involved. The article also sheds light on the emotional and affective aspects involved in the translation process, highlighting the recurring theme of trust and the fear of translatorial non-compliance. Through examples, it demonstrates how authors can actively engage in the translation process to safeguard their narrative nuances. Case studies, including instances involving Umberto Eco, Guillermo Cabrera Infante, Carlos Fuentes, and Günter Grass, illustrate various levels of authorial control and collaboration. The discussion expands to the global literary landscape, emphasising the dominance of certain languages and the dynamics between the literary centre and periphery. Ultimately, it raises fundamental questions about authorship, control, and the transformative power of translation in shaping the “world republic of letters”. The article investigates the multifaceted dynamics between authors and translators, examining collaboration along a continuum from carte blanche to conflictual relationships. The extent of an author’s involvement in the translation process is explored, questioning the reasons behind some authors’ keen interest in ensuring accurate translations. The power imbalances within collaborations are scrutinised, raising questions about the translator’s agency. The article concludes with reflections on the challenges and potential pitfalls of authors participating in the translation of their own works, emphasising the inherent plurality of interpretations in the act of translation.